Ultrasound of entheses in ankylosing spondylitis patients: The importance of the calcaneal and quadriceps entheses for differentiating patients from healthy individuals - Ishida, Suellen Narimatsu (Clinics (Sao Paulo), 2019)
OBJECTIVES: To compare the ultrasonographic findings of entheses in ankylosing spondylitis (AS) patients with those of healthy control individuals and to assess the ability of ultrasound (US) to identify aspects related to the disease. METHODS: A cross-sectional study involving 50 patients with AS and 30 healthy controls was performed. Clinical assessment included the use of a visual analog scale for pain, assessment of swelling of the enthesis, global assessments for patients and physician, use of a disease activity index, mobility and dysfunctional indices, erythrocyte sedimentation rate and clinical enthesitis index. US was performed for the following entheses by two experienced musculoskeletal radiologists: brachial triceps, distal quadriceps, proximal and distal patellar tendons, calcaneal tendon, and plantar fascia; the total and subitems of the Madrid Sonographic Enthesitis Index were used for evaluations. RESULTS: Comparison between groups showed a statistically significant difference with worse scores in AS patients, with bone erosion of the calcaneal enthesis and bone erosion and thickening of the plantar fascia. The odds ratio for thickening of the plantar fascia in the AS group was 3.47, according to logistic regression analysis. The AS group also had worse scores regarding the presence of calcification in the quadriceps enthesis, with a fivefold increased risk. CONCLUSION: US analysis showed that only entheses of the foot and quadriceps were able to differentiate AS patients from healthy individuals.